2006
DOI: 10.1007/s00415-006-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep gray matter and fatigue in MS

Abstract: The median T1 in the thalamus and the putamen were significantly higher in the patient cohort than in the healthy controls; the median T1 in the caudate was also higher in the MS patients but did not reach statistical significance. There was a significant correlation between fatigue severity and the T1 of the thalamus (rho = 0.418; p = 0.014). Furthermore, the median T1 in the thalamus was significantly higher in patients with fatigue compared with those without (p = 0.018). Our results provide further evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 44 publications
5
60
0
5
Order By: Relevance
“…In the last decade several studies were conducted investigating the association between fatigue and brain pathology. Most of these studies are designed cross-sectional and found, similar to our results, no correlation between fatigue severity and conventional MRI parameters such as the extent and location of T2 lesions [2,8,9,27,37,39,40], the occurrence of contrast enhancing lesions [23] or brain atrophy [2,40]. Only one study could demonstrate higher T2 lesion burden in 15 non-disabled MS patients with fatigue compared to 15 patients without [10] with a correlation coefficient of 0.5 (p \ 0.005).…”
Section: Discussionsupporting
confidence: 86%
“…In the last decade several studies were conducted investigating the association between fatigue and brain pathology. Most of these studies are designed cross-sectional and found, similar to our results, no correlation between fatigue severity and conventional MRI parameters such as the extent and location of T2 lesions [2,8,9,27,37,39,40], the occurrence of contrast enhancing lesions [23] or brain atrophy [2,40]. Only one study could demonstrate higher T2 lesion burden in 15 non-disabled MS patients with fatigue compared to 15 patients without [10] with a correlation coefficient of 0.5 (p \ 0.005).…”
Section: Discussionsupporting
confidence: 86%
“…Magnetic resonance imaging (MRI) studies for example revealed a strong correlation between gray matter atrophy and future disability progression (Amato et al, 2007;Fisher et al, 2008). Gray matter pathology has further been linked with physical disability and cognitive impairment (Pirko et al, 2007) as well as fatigue (Roelcke et al, 1997;Filippi et al, 2002;Niepel et al, 2006), which are common manifestations of MS (Wishart and Sharpe, 1997;Blinkenberg et al, 2000;Lazeron et al, 2000;Amato et al, 2004;Benedict et al, 2004;Morgen et al, 2006;Sanfilipo et al, 2006;Houtchens et al, 2007). However, to date the precise pathological alterations underlying these manifestations is not known.…”
Section: Discussionmentioning
confidence: 97%
“…Besides that, diffuse white and gray matter abnormalities in non-lesional normally myelinated areas have been gaining increasing attention (Graumann et al, 2003;Stadelmann et al, 2008;Zeis et al, 2008Zeis et al, , 2009). In the case of the non-lesional normal appearing gray matter (NAGM) of MS patients little is known about the molecular changes which possibly precede gray matter lesion formation (Dutta et al, 2006(Dutta et al, , 2007 and potentially contribute to clinical features encountered in MS. Of those, gray matter pathology has been linked with physical disability and cognitive impairment (Pirko et al, 2007) as well as fatigue (Roelcke et al, 1997;Filippi et al, 2002;Niepel et al, 2006), which are common manifestations of MS (Wishart and Sharpe, 1997;Blinkenberg et al, 2000;Lazeron et al, 2000;Amato et al, 2004;Benedict et al, 2004;Morgen et al, 2006;Sanfilipo et al, 2006;Houtchens et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Niepel et al used the significant correlation between the T1 relaxation time and increased disability to measure fatigue severity in relapsing-remitting MS (RRMS) patients. They exclusively looked at structures within the deep grey matter and found that the T1 relaxation times within the thalamus correlated with worsened fatigue (p = 0.014) [34]. Both Téllez's and Niepel's work suggest that the deep grey matter plays a role in the pathogenesis of fatigue in MS.…”
Section: Cerebral Lesionsmentioning
confidence: 95%